Study protocol for a multicenter randomized controlled trial on simulation-based communication training for pediatric cardiology trainees (SIMUL-CHD) - Paul Padovani; Quentin Hauet; Bruno Lefort; Anne Chauviré-Drouard; Marine Letellier; Marie Bergé; Gaëlle Marguin; Myriam Titos; Audrey Grain; Marie-Lise Babonneau; Claire-Cécile Michon; Mathilde Trosdorf; et al. (BMC Medical Education)
Abstract Background Effective physician-patient communication is crucial to compassionate healthcare, particularly when conveying life-altering diagnoses such as those associated with congenital heart diseases. Despite its importance, medical practitioners often face challenges in communicating effectively. Because of these gaps, we aim to introduce a simulation-based training protocol to improve pediatric cardiology trainee’s communication skills. This study will be conducted in collaboration with associations supporting caregivers of children with congenital heart disease. It strives to demonstrate how specific training programs can efficiently foster humanistic, patient-centered care in standard medical practice. Methods This multicenter, open-label randomized controlled trial will be conducted in pediatric cardiac units and simulation centers of across 10 universities in France. The study population comprises pediatric cardiologists in training (including pediatric cardiac fellows or specialist assistants). The SIMUL-CHD intervention will consist of simulation-based training with standardized patients, focusing on improving communication skills for pediatric cardiology trainees during diagnostic counselling. Patients and caregivers have been recruited from a National Patient Association named “Petit Cœur de Beurre”. The primary outcome is the quality of physicians’ communication skills. The evaluation committee, which will review video recordings of the sessions, will be blinded to which participants received simulation-based training (group of interest) and which received theory-based training (control group). Secondary outcomes are the effect of SIMUL-CHD on empathy and anxiety levels in young pediatric cardiologists. Baseline scores pre and post-intervention will be compared, and skill improvement resulting from the intervention measured. Discussion Simulation-based training has proven efficacy in teaching technical skills in various scenarios however its application to communication skills in pediatric cardiology remains unexplored. The involvement of experienced parents provides a unique perspective, incorporating their profound understanding of the emotional challenges and specific hurdles faced by families dealing with congenital heart disease. Trial registration This trial is registered with the OSF registry (registered https://osf.io/ed78q ).